Procedural fairness and political attitudes: unpacking the experiences of victims of intimate partner violence with the police - Rabello Kras, Helen (Revista Latinoamericana de Opinión Pública, 2024)
What is the relationship between procedural fairness in encounters with the police and intimate partner violence (IPV) survivors’ attitudes? I argue that because of the emotional damage caused by victimization, survivors are especially attuned to the interpersonal treatment they receive when seeking help from specialized services (e. g., police). If this treatment is procedurally unfair, they might conclude that IPV laws are not effective and become less likely to report intentions to intervene by calling the police if they witness intimate partner violence. Relying on public opinion data from Brazil, I find that procedural fairness matters for survivors’ opinions about laws, but I found no relationship between procedural fairness and bystander intervention attitudes. I explore possible explanations for this non-finding with several additional analyses.